Paired immunoglobulin-like receptor B inhibits IL-13–driven eosinophil accumulation and activation in the esophagus - Ben Baruch-Morgenstern, Netali (J Immunol, 2016)
Eosinophilic esophagitis (EoE) is a T helper type 2 (Th2) cytokine–associated disease characterized by eosinophil infiltration, epithelial cell hyperplasia and tissue remodeling. Recent studies have highlighted a major contribution for IL-13 in EoE pathogenesis. Paired immunoglobulin-like receptor (PIR)-B is a cell surface immune-inhibitory receptor that is expressed by eosinophils and postulated to regulate eosinophil development and migration. We report that Pirb is upregulated in the esophagus after inducible overexpression of IL-13 (CC10-Il13(Tg) mice) and is overexpressed by esophageal eosinophils. CC10-Il13(Tg)/Pirb(−)(/)(−) mice displayed increased esophageal eosinophilia and EoE pathology, including epithelial cell thickening, fibrosis and angiogenesis, compared with CC10-Il13(Tg)/Pirb(+/+) mice. Transcriptome analysis of primary Pirb(+/+) and Pirb(−)(/)(−) esophageal eosinophils revealed increased expression of transcripts associated with promoting tissue remodeling in Pirb(−)(/)(−) eosinophils including pro-fibrotic genes, genes promoting epithelial-to-mesenchymal transition (EMT) and genes associated with epithelial growth. These data identify PIR-B as a molecular checkpoint in IL-13–induced eosinophil accumulation and activation, which may serve as a novel target for future therapy in EoE.